A learning outcome assessment information system to facilitate Outcome-Based Education (OBE) implementation - Berlian Kushari; Lukman Septiadi (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Assessment is an integral part of an outcome-based education (OBE) system. It helps ensuring student learning and ultimately attaining the expected outcomes at the time of graduation. Records of assessment results enable a study program to conduct continual improvement of its education activities. This paper reports the development of an information system and technology that helped Civil Engineering Program of Islamic University of Indonesia to ensure Program Learning Outcomes (PLO) attainment by its students in its gear towards obtaining an international accreditation. The system was implemented as an online web application that includes students, faculty, student advisors, and program manager as the users. The system allows to, firstly, define the PLOs, their performance indicators (PI), and the scoring system of PLO attainment, including setting up of required minimum attainment level. Secondly, for each PLO, a road map that defines the structural relationship between all PLO PIs and the selected courses throughout the semesters in which those indicators are to be measured (i.e. as course learning outcomes) must be defined. Once these relationships are firmly fixed and mapped, the system is ready to assist the program manager, student advisors, and individual students to conduct monitoring and evaluation (self-evaluation in student’s case) of program and course learning outcomes achievement. System’s important features are highlighted along with discussion on development strategies, current operational status, as well as challenges for future development.